PENGARUH MODEL PEMBELAJARAN MAKE A MATCH DENGAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 1 SIDAMANIK - Mustika Piliang, Fenny; Romlayani (Jurnal Metabio, 2021)
This study aims to determine the effect of the make-a-match learning model with picture and picture on student learning outcomes in the excretory system in eighth-grade students at SMP Negeri 1 Sidamanik. The population in this study was 311 students, and the sample size was 64 students (cluster random sampling). Class VIII-B served as Experimental Class I and VIII-C as Experimental Class II. Data analysis was performed by calculating the mean, median, mode, and standard deviation. Hypotheses were tested using statistics or the t-test at a significance level of α = 0.05. The average pre-test score for Experimental Class I was 45.63 and for Experimental Class II was 42.34. The post-test score for Experimental Class I was 81.88 and for Experimental Class II was 81.56, a difference of 3.2%. The results of the hypothesis test using the t-test obtained t-count (103.1) > (1.669). Therefore, Ha is accepted and Ho is rejected, indicating that the make a-match learning model with picture and picture has an effect on student learning outcomes at SMP Negeri 1 Sidamanik. Based on the research results and data analysis, it was concluded that the make-a-match learning model with picture and picture has an effect on student learning outcomes at SMP Negeri 1 Sidamanik.